Comprehensive structural study of lanthanide(III) chloride hydrates: [RECl3·xH2O (RE = La–Nd, Sm–Lu; x = 6, 7)] - Thimira Kandabadage; Beau Legnon; Sviatoslav Baranets (Acta Crystallographica Section E: Crystallographic Communications)
A comprehensive crystallographic study is presented of the complete series of rare-earth(III) chloride hydrates. Early lanthanides form dimeric [(H2O)7RE(μ-Cl)2RE(H2O)7]4+ binuclear complexes in which each RE atom (RE = La3+, Ce3+) is coordinated by seven H2O molecules and two bridging inner-sphere chloride ions. Di-μ-chlorido-bis[heptaaqualanthanide(III)] tetrachloride, [(H2O)7RE(μ-Cl)2RE(H2O)7]Cl4, crystallizes in the triclinic space group P1. Heavier lanthanides exhibit monomeric [RECl2(H2O)6]+ units where each RE atom (RE = Pr3+, Nd3+, Sm3+–Lu3+) is coordinated by six H2O molecules and two inner-sphere chloride ions. Hexaaquadichloridolanthanide(III) chlorides, [RECl2(H2O)6]Cl, adopt the monoclinic space group P2/c. In both structures, the cationic inner-sphere complex is counter-charged by the corresponding number of outer-sphere Cl− anions, in which the metal ion and outer-sphere chloride ion lie on crystallographic twofold axes. Crystal structures for all compounds were determined in high quality with refined H-atom positions and were collected at the same temperature (100 K), providing a uniform structural dataset and addressing discrepancies in previous reports. The crystal structure of [HoCl2(H2O)6]Cl is reported for the first time.